Evaluation of antifibrotic and antifungal combined therapies in experimental pulmonary paracoccidioidomycosis - Finato, Angela C. [UNESP]; Almeida, Débora F [UNESP]; Dos Santos, Amanda R. [UNESP]; Nascimento, Dejair C.; Cavalcante, Ricardo S. [UNESP]; Mendes, Rinaldo P. [UNESP]; Soares, Cléverson T; Paniago, Anamaria M M; Venturini, James (Oxford University Press (OUP), 2020)
Paracoccidioidomycosis (PCM) is a systemic mycosis caused by the Paracoccidioides genus. Most of the patients with chronic form present sequelae, like pulmonary fibrosis, with no effective treatment, leading to impaired lung functions. In the present study, we aimed to investigate the antifibrotic activity of three compounds: pentoxifylline (PTX), azithromycin (AZT), and thalidomide (Thal) in a murine model of pulmonary PCM treated with itraconazole (ITC) or cotrimoxazole (CMX). BALB/c mice were inoculated with P. brasiliensis (Pb) by the intratracheal route and after 8 weeks, they were submitted to one of the following six treatments: PTX/ITC, PTX/CMX, AZT/ITC, AZT/CMX, Thal/ITC, and Thal/CMX. After 8 weeks of treatment, the lungs were collected for determination of fungal burden, production of OH-proline, deposition of reticulin fibers, and pulmonary concentrations of cytokines and growth factors. Pb-infected mice treated with PTX/ITC presented a reduction in the pulmonary concentrations of OH-proline, associated with lower concentrations of interleukin (IL)-6, IL-17, and transforming growth factor (TGF)-β1 and higher concentrations of IL-10 compared to the controls. The Pb-infected mice treated with AZT/CMX exhibited decreased pulmonary concentrations of OH-proline associated with lower levels of TGF-β1, and higher levels of IL-10 compared controls. The mice treated with ITC/Thal and CMX/Thal showed intense weight loss, increased deposition of reticulin fibers, high pulmonary concentrations of CCL3, IFN-γ and VEGF, and decreased concentrations of IL-6, IL-1β, IL-17, and TGF-β1. In conclusion, our findings reinforce the antifibrotic role of PTX only when associated with ITC, and AZT only when associated with CMX, but Thal did not show any action upon addition.
Keywords: Paracoccidioides brasiliensis; azithromycin; cotrimoxazole; itraconazole; pentoxifylline; pulmonary fibrosis; thalidomide